2019
DOI: 10.1080/10409289.2019.1624145
|View full text |Cite
|
Sign up to set email alerts
|

Language Abilities and Peer Rejection in Kindergarten: A Mediation Analysis

Abstract: Rejection by peers has devastating effects on children's social-cognitive development. As language difficulties have been found to be one of the underlying causes of peer rejection, the present study focused on the relation between these two variables. Specifically, this study was the first to test a hypothesized model connecting children's level of receptive vocabulary knowledge to the extent to which they are rejected by their peers, through their ability to communicate effectively. A sample of N = 135 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…Evidence of validity based on test-criterion relationships was collected by analyzing the effects of the child's gender, maternal education, and birth order on the CDI-III-PT scores. No gender differences were found in any of the two subscales, supporting the findings of other studies that suggest that boys catch up to girls' language abilities in preschool years (Altinkaynak, 2019;Fung et al, 2019;Jin et al, 2020;van der Wilt et al, 2020). Significant effects were found for maternal education in both subscales, a result which is also congruent with the findings of previous research in early development (Umek et al, 2006;Weigel et al, 2006;Fenson et al, 2007;Richels et al, 2013;Andonova, 2015;Gonzalez et al, 2017;Cadime et al, 2018;Farley and Piasta, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Evidence of validity based on test-criterion relationships was collected by analyzing the effects of the child's gender, maternal education, and birth order on the CDI-III-PT scores. No gender differences were found in any of the two subscales, supporting the findings of other studies that suggest that boys catch up to girls' language abilities in preschool years (Altinkaynak, 2019;Fung et al, 2019;Jin et al, 2020;van der Wilt et al, 2020). Significant effects were found for maternal education in both subscales, a result which is also congruent with the findings of previous research in early development (Umek et al, 2006;Weigel et al, 2006;Fenson et al, 2007;Richels et al, 2013;Andonova, 2015;Gonzalez et al, 2017;Cadime et al, 2018;Farley and Piasta, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…No gender differences were found in any of the two subscales, supporting the findings of other studies that suggest that boys catch up to girls' language abilities in preschool years (Altinkaynak, 2019;Fung et al, 2019;Jin et al, 2020;van der Wilt et al, 2020). Significant effects were found for maternal education in both subscales, a result which is also congruent with the findings of previous research in early development (Umek et al, 2006;Weigel et al, 2006;Fenson et al, 2007;Richels et al, 2013;Andonova, 2015;Gonzalez et al, 2017;Cadime et al, 2018;Farley and Piasta, 2020). Regarding birth order, a significant effect was found in vocabulary, indicating that the advantage in lexical abilities of first born children which has been found in toddlers (Fenson et al, 1994;Hoff-Ginsberg, 1998;Berglund et al, 2005;Zambrana et al, 2012) is maintained at least until the fourth year of age.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This raises the question of whether the association between language and social problems is dependent on developmental age or type of language difficulty. When investigating how different aspects of language were linked to peer rejection, van der Wilt et al (2020) found that children's vocabulary knowledge (receptive skills) was indirectly associated with peer rejection through oral communicative competence (expressive skills). Furthermore, Rennecke et al (2019) found that both receptive and expressive language disorders were associated with peer victimization and bully perpetration.…”
mentioning
confidence: 99%